Care during the decision-making phase for women who want a vaginal breech birth: Experiences from the field. (March 2016) - Catling, C.; Petrovska, K.; Watts, N.P.; Bisits, A.; Homer, C.S.E.
Abstract: Background: few women are given the option of a vaginal breech birth in Australia, unless the clinicians feel confident and have the skills to facilitate this mode of birth. Few studies describe how clinicians provide care during the decision-making phase for women who choose a vaginal breech birth. The aim of this study was to explore how experienced clinicians facilitated decisions about external cephalic version and mode of birth for women who have a breech presentation. Methods: a descriptive exploratory design was undertaken with nine experienced clinicians (obstetricians and midwives) from two tertiary hospitals in Australia. Data were collected through face to face interviews and analysed thematically. Findings: five obstetricians and four midwives participated in this study. All were experienced in caring for women having a vaginal breech birth and were currently involved in providing such a service. The themes that arose from the data were: Pitching the discussion, Discussing safety and risk, Being calm and Providing continuity of care . Conclusions: caring for women who seek a vaginal breech birth includes careful selection of appropriate women, full discussions outlining the risks involved, and undertaking care with a calm manner, ensuring continuity of care. Health services considering establishing a vaginal breech service should consider that these elements are included in the establishment and implementation processes. Highlights: Experienced clinicians discussed how they cared for women having a breech birth. Individualised risk and safety information regarding breech birth was vital. Information needed to encompass women's needs, values and personal contexts. Decision-making needed to be based on current evidence. Framing risk in a calm manner and providing continuity of care was important.